2006
DOI: 10.1002/cbf.1377
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caffeic acid phenethyl ester on treatment of experimentally induced methicillin‐resi̇stant Staphylococcus epidermidis endophthalmitis in a rabbit model

Abstract: This study investigated the anti-inflammatory effects of caffeic acid phenethyl ester (CAPE), a natural bee-produced compound, and compared it with corticosteroids in the treatment of experimentally induced methicillin-resistant Staphylococcus epidermidis (MRSE) endophthalmitis in addition to intravitreal antibiotics. An experimental endophthalmitis model was produced in 24 New Zealand albino rabbits by unilateral intravitreal injection of 0.1 ml of 4.7 x 10(4) colony-forming units (CFU) methicillin-resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Many research studies have shown that the properties of these polyphenols and propolis itself display antibacterial, antioxidative, antiviral, antibacterial, anti-inflammatory, antiplatelet, antineoplastic, as well as antitumor activities. 34 - 40 Moreover, a diet rich in polyphenols and flavonoids from natural sources (plant foods and bee products) may represent a protective lifestyle, which can promote (breast) cancer chemoprevention as well as show promise that anticancer phytotherapeutics might be developed from food. 41 …”
Section: Introductionmentioning
confidence: 99%
“…Many research studies have shown that the properties of these polyphenols and propolis itself display antibacterial, antioxidative, antiviral, antibacterial, anti-inflammatory, antiplatelet, antineoplastic, as well as antitumor activities. 34 - 40 Moreover, a diet rich in polyphenols and flavonoids from natural sources (plant foods and bee products) may represent a protective lifestyle, which can promote (breast) cancer chemoprevention as well as show promise that anticancer phytotherapeutics might be developed from food. 41 …”
Section: Introductionmentioning
confidence: 99%
“…Two of these are caffeic acid (CA) and the caffeic acid phenethyl ester (CAPE). Some of their properties reported in research include: antioxidative, antibacterial, antiviral, anti-inflammatory, antiplatelet, antitumor, and antineoplastic effects [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This compound was first synthesized in 1988 [18]. It is characterized by strong biotic properties, including the following: antibacterial [19], antiviral [20], anti-inflammatory [21], antioxidative [22], antiplatelet [23] and antitumor [24,25].…”
Section: Introductionmentioning
confidence: 99%